The vascular epiphyte flora in a white-sand ecosystem of the Uatumã Sustainable Development Reserve, Central Amazon - Viviane Pagnussat Klein; Layon Oreste Demarchi; Adriano Costa Quaresma; Jefferson da Cruz; Maria Teresa Fernandez Piedade (Check List, 2022)
Amazon ecosystems have suffered constant losses due to fragmentation processes, which as a result puts associated biodiversity at risk. Although vascular epiphytes constitute a representative component of tropical forests, they are still poorly studied in white-sand ecosystems. We present a description and checklist of the vascular epiphytes present in white-sand ecosystems (campinaranas) in the Central Amazon. We also analyzed the structure and determined of the value of epiphytic importance (VEI) for the species. We recorded 112 species, 58 genera, and 16 families of vascular epiphytes. The greatest richness (95 spp.) was observed in forested phytophysiognomies. Orchidaceae (66 spp.), Bromeliaceae (12 spp.), and Araceae (9 spp.) were the richest families. Prosthechea aemula W.E.Higgins (Orchidaceae) had the highest VEI and accounted for about 28% of an abundance of individuals. Among the species, 36.6% have a distribution restricted to the Amazon region, which emphasizes the importance of the conservation of these environments.